Construyendo una STEAM-E-WEB (Science, Technology, Engineering, Art, Mathematics-English Web) - Saborío Taylor, Silvia; García Borbón, Marcela (Innovaciones Educativas, 2021)
The purpose of this article is to provide a guide for the development of educational projects based on the STEM/STEAM methodology based on the experience of designing the STEAM-E-WEB project, which also articulates the communication skills of the English language. It is intended to be implemented with juniors. The design of the STEAM-E-WEB project started from the analysis of the skills and competencies of the 21st century, the learning environments and the didactic strategies that favor the development of STEM/STEAM methodologies. The methodology used for the design of the project consisted of three stages: definition of the implementation model and selection of teaching strategies, evaluation of the project as a proposal and delimitation of the final project proposal. One of the most important results of the STEAM-E-WEB project is that it allows expanding interdisciplinary work. It includes the English language within the areas of the STEM/STEAM methodology, as a complement to the development of the student’s skills. Among the main conclusions it can be mentioned that the projects designed under the STEM/STEAM methodology promote the active, conscious and responsible participation of the students. Likewise, it constitutes an opportunity for teachers from different disciplines to interact in favor of a comprehensive teaching and learning process for those involved.